Localization Of The Global Nursing Process In Malaysian Context: Student Nurses Perspectives - Thet, Lynn Lynn; Razak, Ahmad Zabidi Abdul; Jamaluddin, Shahrir; Ghavifekr, Simin (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
The term nursing process was first used in North America during the 1950s-1960s. It has now been widely adopted worldwide as a global concept. In Malaysia, their Department of Higher Education has set the agenda and adopts the nursing process to upgrade Malaysian nursing from functional to professional standard. Implementation was commenced in 2010 and targeted the fresh graduate nurses who would apply the nursing process by 2016. Therefore, this study aims to highlight the factors that influence and mediate in the application of nursing process among student nurses. A cross-sectional survey was conducted using a structured questionnaire in East and West Malaysia in 2015. Altogether, 468 student nurses actively participated in the study. A multiple regression analysis was conducted to identify the factors influencing the nursing process. The Sobel test mediation identified the mediating factor on translating knowledge to practice of nursing process. The findings prove that the student nurses’ knowledge about the core concepts of nursing process, attitude towards nursing process and its implementation process, and the factors that support in implementation process are influencing their application of nursing process. Beyond that, the indirect mediation effect (supporting factor as a mediator) is existing in a relationship between applying knowledge into practice. This research indicates that providing the necessary support is principally important in enhancing the application of nursing process in Malaysian nursing context.